Direct Synthesis of N-Functionalized Dipropargylamine Linkers as Models for Use in Peptide Stapling - Renzetti, Andrea; Rutherford, Ryan N.; Fukumoto, Kozo; Kunciw, Dominique; Sore, Hannah F.; Spring, David R. (Synlett, 2019)
N-Substituted dipropargylamines that are suitable as functionalized linkers for peptide stapling can be synthesized in one step under mild conditions from commercially available starting materials (41% to quantitative yield).
Keywords: peptides; stapling; linkers; amines; alkynes; click chemistry